A Comprehensive Review on Inkjet‐Printed Intelligent Food Packaging Materials: Principle, Ink Formulation, Functional Inks, and Potential Applications - Siyi Liu; Zhenyu Han; Xiaoyu Luo (Food Frontiers)
ABSTRACT Food packaging is crucial for preserving food quality, safety, and integrity while meeting consumer demands for convenience and sustainability. Innovative packaging systems can enhance the basic packaging characteristics; in particular, intelligent packaging meets the rising demands to improve the communication and convenience functions of food packaging by integrating real‐time monitoring and interactive features. Inkjet printing can be a potential means for the incorporation of such intelligent packaging add‐ons. As a liquid deposition process, the adoption of inkjet printing in intelligent packaging requires the formulation of printable inks that are compatible with various printing substrates. Hence, this review article aims to comprehensively discuss the fundamental principles and requirements of inkjet printed materials for their application in intelligent packaging development. By optimizing ink composition with desired rheological characteristics, printable fluids can be successfully formulated if a compatible printing substrate is selected. Different types of functional inks that are chromogenic, luminescent, or conductive can be promising in developing inkjet‐printed intelligent materials in the form of indicators, sensors, or bar codes. Overall, inkjet‐printed functional inks can become a promising material in intelligent packaging development for the packaging industry, such as for monitoring food safety issues, revealing freshness decay, detecting potential adulterants, and tracking product status in the supply chain. Future research may focus on developing stable biodegradable inks, incorporating artificial intelligence features, and scaling up for industrial applications.